Liquidity of the CBOE Equity Options - Vijh, Anand M. (Journal of Finance, 1990)
We examine the CBOE option market depth and bid-ask spreads. Absence of price effects surrounding large option trades suggests excellent market depth. However, bid-ask spreads for the CBOE options and the NYSE stocks are nearly equal, even though an average option is equivalent to less than half a stock plus borrowing. We explain this tradeoff between market depth and bid-ask spreads on the CBOE and the NYSE by differences in market mechanisms. We also show that the adverse-selection component of the option spread, which measures the extent of information-related trading on the CBOE, is very small.